Post-pandemic insights on COVID-19 and premature ovarian insufficiency - Han Yaguang; Dai Yang; Wang Kexin; Zhang Xin; Shao Zishen; Zhu Xiaolin (Open Life Sciences)
The COVID-19 pandemic has raised concerns regarding its potential impact on premature ovarian insufficiency (POI). This overview examines the possible interactions between COVID-19 and POI, while also suggesting preventive measures. The viral infection’s inflammatory response and immune dysregulation may adversely affect ovarian tissues, leading to inflammation and damage. Additionally, alterations in vascular function could impair ovarian blood flow and hormonal imbalances may disrupt normal ovarian function. Long-term health effects, such as “long COVID,” may exacerbate these issues through chronic inflammation and immune dysfunction. Public health measures, such as vaccination and home isolation, may indirectly protect ovarian health by reducing systemic inflammation. Vaccines could mitigate the severity of COVID-19’s impact on ovarian function, while isolation may reduce stress and inflammation. However, further research is needed to validate these mechanisms.